Pemberdayaan Mahasiswa BDP FPIK UHO dalam menerapkan Teknologi Sistem Hidroponik pada Kelompok Milenial Desa Tapulaga, Kabupaten Konawe Selatan, Sulawesi Tenggara - Muskita, Wellem H; Muhaimin Hamzah; La Ode Aslin; Sofiyan (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
AbstractThis community service program aims to enhance the knowledge and skills of the millennial group inTapulaga Village, South Konawe Regency, in applying hydroponic system technology as an environmentallyfriendly and productive business alternative. The topic was chosen based on the low utilization of modernagricultural technology among rural youth and the high potential of coastal areas for developing sustainableagribusiness ventures. The activity was conducted by students of Aquaculture Study Program (BDP), Facultyof Fisheries and Marine Science, Universitas Halu Oleo (UHO), through a participatory approach involvingsocialization, technical training on hydroponic installation, plant maintenance assistance, and evaluation ofplant growth results. The results showed an 85% increase in participants’ understanding of the basic conceptsof hydroponics, and 70% of participants were able to operate the system independently. Moreover, themillennial group began to show interest in developing hydroponics as a new business opportunity in the village.This program has had a positive impact in promoting economic independence and strengthening the capacityof young generations through the application of appropriate technology in modern agriculture. Keywords: Hydroponics, Innovation, Millennials, Empowerment, Appropriate Technology